2020
DOI: 10.3390/rs12101647
|View full text |Cite
|
Sign up to set email alerts
|

Suitability of Airborne and Terrestrial Laser Scanning for Mapping Tree Crop Structural Metrics for Improved Orchard Management

Abstract: Airborne Laser Scanning (ALS) and Terrestrial Laser Scanning (TLS) systems are useful tools for deriving horticultural tree structure estimates. However, there are limited studies to guide growers and agronomists on different applications of the two technologies for horticultural tree crops, despite the importance of measuring tree structure for pruning practices, yield forecasting, tree condition assessment, irrigation and fertilization optimization. Here, we evaluated ALS data against near coincident TLS dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 68 publications
1
17
0
Order By: Relevance
“…Existing solutions for improving the completeness of data can be divided into two groups: the first is to densify the data collection such as to add multiple viewing angles of scanner in order to enhance canopy and stem completeness, e.g., (Roşca et al 2018;Wu et al 2020), or to densify trajectories in order to record more trees from more viewing perspectives, e.g., (Morsdorf et al 2017;Del Perugia et al 2019;Kuželka et al 2020); The second is the fusion of datasets from different platforms, especially between terrestrial and aerial platforms, e.g., (Paris et al 2017;Giannetti et al 2018;Dai et al 2019;Pyörälä et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Existing solutions for improving the completeness of data can be divided into two groups: the first is to densify the data collection such as to add multiple viewing angles of scanner in order to enhance canopy and stem completeness, e.g., (Roşca et al 2018;Wu et al 2020), or to densify trajectories in order to record more trees from more viewing perspectives, e.g., (Morsdorf et al 2017;Del Perugia et al 2019;Kuželka et al 2020); The second is the fusion of datasets from different platforms, especially between terrestrial and aerial platforms, e.g., (Paris et al 2017;Giannetti et al 2018;Dai et al 2019;Pyörälä et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The value of V VB falls within the mid-range for volume measurement, but it also required the longest run time (T VB = 4.867s) which fluctuated greatly. Therefore, the VB algorithm could be selected to calculate canopy volume off-line, and to precisely measure relevant parameters of leaves, such as leaf area and LAD [39,59]. The AS algorithm can better express the actual shape of the actual canopy.…”
Section: Running Time Analysis Of Apcsmentioning
confidence: 99%
“…In addition, traits such as crown density and structural complexity were found to be associated with the genetic diversity within and between species. Wu et al (2020a) evaluated the ability of ALS and TLS data to assess the crown structure traits of individual fruit trees, including avocado trees, macadamia trees, and mango trees. Their study showed that ALS and TLS both provided similar crown area, fractional cover, and maximum crown height (R 2  0.94, relative RMSE  4.47%), while the crown volume estimations were less correlated (R 2 = 0.81, relative RMSE = 42.66%), with the ALS approach underestimating such data compared to the TLS data, primarily due to the limited capacity of ALS data to measure lower branches and the within-canopy structure.…”
Section: Time Of Flight Sensor-based Datamentioning
confidence: 99%
“…In addition, canopy height from reconstructed 3D shape models is used to evaluate crop water status for irrigation planning. It can also be used as a guideline for sprayer settings to achieve a suitable spray volume and timing and as a variable to set the operation of harvesting machines and for pruning tasks in tree fruit orchards (Zhang et al, 2018;Aboutalebi et al, 2020;Pereira et al, 2020;Wu et al, 2020aWu et al, , 2020b.…”
Section: Tree Heightmentioning
confidence: 99%
See 1 more Smart Citation